Red cell distribution width (RDW) and Alberta stroke programme early computed tomography score (ASPECTS) are correlated in predicting mortality in geriatric ischemic stroke patients (Annals of Medical Research, 2022)
Aim: Ischemic stroke is one of the leading causes of death and disability in elderly people worldwide. The aims of this study were to investigate the relationship of hematologic parameters and Alberta Stroke Programme Early Computed Tomography Score (ASPECTS) with mortality in geriatric patients suffering an ischemic stroke.Materials and Methods: Geriatric ischemic stroke patients referring to our hospital between May 2016 and May 2019 were retrospectively analyzed. ROC curve analysis was performed to determine the predictive value of hematologic parameters with respect to in-hospital mortality. Multivariate logistic regression analysis was performed to determine the independent predictors of in-hospital mortality.Results: The neutrophil count, monocyte count, red cell distribution width, neutrophil-lymphocyte ratio and monocyte-lymphocyte ratio were significantly higher, whereas the lymphocyte count was significantly lower in patients who died in the hospital than in those who did not. The areas under the curve for the red cell distribution width, neutrophil-lymphocyte ratio, and monocyte-lymphocyte ratio were 0.720, 0.643, and 0.660, respectively. In the logistic regression analysis, age, female sex, ASPECTS, monocyte-lymphocyte ratio and red cell distribution width were identified as independent predictors of in-hospital mortality. In the correlation analysis, a weak negative correlation was found between the ASPECTS and the red cell distribution width (r = 0.303, p < 0.001).Conclusion: The red cell distribution width, monocyte-lymphocyte ratio, and ASPECTS are independent predictors of in-hospital mortality in geriatric ischemic stroke patients. There is a correlation between the ASPECTS and the red cell distribution width.
Keywords: Cerebrovascular disease; Stroke; Mortality; Red cell distribution width